Implementation of the CIPP Model for Assessing the Elements of Archive Management Based on The Independent Curriculum - Destya Selviana, Ananda; Ismiyati; Sholikah, Mar'atus (Jurnal Pendidikan dan Pengajaran, 2025)
Learning evaluation is a process that must be carried out for teachers to assess the achievement of learning objectives and optimize the program based on evaluation results. This research aims to analyze the evaluation of the learning program for archiving elements based on the independent curriculum. This research method uses a qualitative approach with the CIPP evaluation model. Data collection techniques are interviews, observation, and documentation. The instrument used is a questionnaire sheet. The subjects involved totaled eight people. The data analysis technique uses interactive analysis. The results showed the Context Aspect, learning is realized in the elements of archival management, learning has not focused on practice, and the importance of archives for the department. Input aspects, teachers compile learning tools, but the content of the teaching module is not in accordance with the learning objectives, the determination of learning strategies, namely PjBL. Process aspects, teacher and learner preparation before learning, learning implementation is not in accordance with the teaching module but learning objectives have been achieved, and there are learning obstacles. Product aspect, there are formative and summative assessments that include cognitive, affective, psychomotor, there are still learning outcomes of students who are not complete, and the use of gas semester report cards that are not appropriate. Therefore, the implementation of this learning still needs to be evaluated continuously in order to achieve optimal learning outcomes.